A longitudinal cohort study of rural adolescent vs adult South African mothers and their children from birth to 24 months - Karl le Roux; Joan Christodoulou; Linnea Stansert-Katzen; Elaine Dippenaar; Christina Laurenzi; Ingrid M. le Roux; Mark Tomlinson; Mary Jane Rotheram-Borus (BMC, 2019)
Abstract Background Adolescent motherhood has been repeatedly linked to poor child outcomes in high income countries and urban areas in low- and middle-income countries. We examine the structural, personal, and caretaking challenges of adolescent mothers and their children in rural South Africa compared to adult mothers over the first 24 months post-birth. Methods A cohort of sequential births (n = 470/493) in the rural OR Tambo District was recruited and reassessed at 3, 6, 9, 12, and at 24 months post-birth, with a retention rate above 84% at all timepoints. Maternal and child outcomes were examined over time using multiple linear and logistic regressions. Results Adolescent mothers reflect 17% of births (n = 76/458). Adolescent mothers were more likely to have water in their households, but less likely to live with a partner and to be seropositive for HIV than adult mothers. Risks posed by mental health symptoms, alcohol, and partner violence were similar. Adolescents exclusively breastfed for shorter time and it took longer for them to secure a child grant compared to adult mothers. Although obtaining immunizations was similar, growth was significantly slower for infants of adolescent mothers compared to adult mothers over time. Conclusions In rural South Africa, almost one in five pregnant women is an adolescent. Caretaking tasks influencing child growth, especially breastfeeding and securing the child grant appear as the greatest problems for adolescent compared to adult mothers.